Pilomatricoma of the cheek reminiscent of histIocytoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Calcifying epithelioma or pilomatricoma is a benign tumor of the hair sheat. It is the most frequent tumor in children and prevail in females after 6 years on the head (1). Its clinical features are usually diagnostic due to its hard consistence, its irregular surface reminiscent of a faceted stone (2) and its color, which can be flesh-colored in the deep lesions or yellow in case of calcification or bluish in case of inflammation (1). Multiple lesions, especially when large and/or ulcered, may be hardly diagnosed (1). Instrumental examinations are usually not useful, although a characteristic ultrasonographic finding with a peripheral hypoechogenic ring and an irregularly echogenic center has been reported (3). In our 2 case, in absence of the most characteristic clinical signs, the histological examination was diriment.